Challenges of Collective Inertia and Scarcity to Technological and Vocational Education Universities - Wu, MingChang; Cassim, Farhad A.K. Joseph; binti Masrul, Suryaneta; Kesa, Deni Danial (Journal of Technical Education and Training, 2021)
The massification of higher education institutions in Taiwan, typically in universities of science and technology, creates competition for resources and currently threatens foreclosures in Taiwan’s higher education system. To answer this challenge amid global competition among universities, the Ministry of Education (MOE) implemented the World-Class Research University Project, creating the initiative for higher education institutions to quickly gain world-class status with the reasonable belief that strong global visibility would attract much needed international resources to supplement local ones. However, the race for global reputation has created highly stressful environments for faculty members to publish research papers in highly regarded international journals. In highlighting fundamental paradoxes of the system and the rationale behind them, this paper attempts to stimulate a much-needed reflection that might pave the way for rational and empirical efforts to transform higher education in Taiwan. This paper also reveals that the emphasis on speed-up achievement has overwhelmed the original academic missions of higher education and placed academics in a scarcity mindset with quantity drowning essence. The primary mechanism for keeping the current system is the collective inertia that limits academics from breaking out of the mould of habitual approaches. This paper discusses all sorts of findings, reported events, theoretical ideas, and inherent contradictions in relation to Taiwan universities in an attempt to frame the essential background on the problems in terms of scarcity mindset and inertial thinking. Finally, the paper provides some suggested solutions. The reflection in this paper may inspire faculty members in higher technological and vocational education programs to lead school administration and industry development with practical and updated knowledge. It is crucial to revitalising faculty members’ educational enthusiasm through building professional autonomy and self-efficacy.